2017
DOI: 10.1007/978-1-4939-7456-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Molecular-Cellular Network Cancer Theory: A Systems Biology Approach

Abstract: In light of ever apparent limitation of the current dominant cancer mutation theory, a quantitative hypothesis for cancer genesis and progression, endogenous molecular-cellular network hypothesis has been proposed from the systems biology perspective, now for more than 10 years. It was intended to include both the genetic and epigenetic causes to understand cancer. Its development enters the stage of meaningful interaction with experimental and clinical data and the limitation of the traditional cancer mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…This hypothesis was applied to study prostate, liver, and gastric cancers, and surprisingly, all cases fitted well with the same core composition [65]. The network resulted in a landscape consisting of many locally (robust) stable normal states and several unhealthy states with no obvious function [52].…”
Section: Endogenous Network Hypothesis (Enh)-far-from Equilibrium Dyn...mentioning
confidence: 88%
See 2 more Smart Citations
“…This hypothesis was applied to study prostate, liver, and gastric cancers, and surprisingly, all cases fitted well with the same core composition [65]. The network resulted in a landscape consisting of many locally (robust) stable normal states and several unhealthy states with no obvious function [52].…”
Section: Endogenous Network Hypothesis (Enh)-far-from Equilibrium Dyn...mentioning
confidence: 88%
“…At present, "the modeling of all interactions remains beyond our capabilities" [51]. The ENH concept was further developed in a subsequent paper by Ping Ao's group (e.g., [52]). Huang et al [53] expanded on the term of attractor state previously proposed by Kaufman as "a set of numerical values toward which a system tends to evolve, for a wide variety of starting conditions of the system."…”
Section: Endogenous Network Hypothesis (Enh)-far-from Equilibrium Dyn...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the evolution of the telencephalon anterior-posterior patterning, we found that such a 5-node network alone is sufficient to draw an answer, but it is not enough for the evolution of the whole central nervous system, let alone the entire vertebrate body plan. The network described in this work can be taken as a subnetwork (Wang et al, 2018), which has the potential to expand into the global decision-making network for the evolution and development of the central nervous system or even the entire vertebrate body plan shaped by evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hematopoietic research about single cell studies are important in last decade but we have some complex in the regenerative system. So, it is better to determine the exact role of involved molecules in clonal expansion and implication of invasion for deconstructing the molecular network including the normal situation to abnormal and malignant stem cells as well [5][6][7][8][25][26][27]. In fact, acute leukemia is a heterogeneous clonal disorder of hematopoietic progenitor cells characterized by proliferation of stem cell as such progenitor cell in bone marrow patients, and so identified a subpopulation of leukemic cells called leukemic stem cells(LSCs).…”
Section: Discussionmentioning
confidence: 99%